Autodesk 3ds Max 2014 Bible - Murdock, Kelly (Bible., 2014)
A complete reference covering the newest version of 3ds Max software Autodesk 3ds Max is the popular 3D modeling, animation, rendering, and compositing software preferred by game developers and graphic designers in film and television. This comprehensive reference not only introduces beginners to this pricey and complex software, but also serves as a reference for experienced users. Packed with expert advice from popular author Kelly Murdock, it begins with a Quick Start tutorial to get you up and running, then continues with more than 150 step-by-step tutorials, advanced coverage.